(untitled) (Nordic Journal of Practical Theology, 2020)
In this article I analyze the relation between narcissistic traits in our culture and preaching of salvation from sin in eight sermons broadcast on Norwegian radio in the period 20072008. The intention has been to investigate how preaching of salvation from sin is going on in a culture with narcissistic traits, and to point out some perspectives and suggestions to promote further theological and homiletic development. The study investigates both how the sermons are affected by narcissistic traits, and how they challenge narcissistic traits in our culture.One main finding is that the preaching of salvation from sin is reduced in many of the sermons. The study also shows how some ministers preach salvation from sin as if salvation is all about fulfilling narcissistic longings. I also show examples of preaching characterized by a lack of insight into narcissistic traits in our culture